Kualitas Mikrobiologis Daging Unggas di RPA dan yang Beredar di Pasaran - E. S., Dewi; S., El Latifa; Fawwarahly, Fawwarahly; Kautsar, R. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2016)
The aim of this study is to determine the microbiological aspect of meat from slaughterhouses to the consumer and to identify the factors and solutions in handling the contamination of meat. In this study the number of psychrotrophs, E, coli, S. aureus in purchased meat in traditional markets and RPA artisanal, has exceeded reasonable limits set out in the guidelines (1996) CNERNA-CNRS poultry meats. Thus in the samples purchased in these sites were regarded as unacceptable quality. Meanwhile Sixty-six samples of chicken meat collected from retailers, 21 samples of chicken breast without skin, 19 samples of chicken breast with skin, and 26 samples of frozen chicken meat 'ground'. The results of analysis, the percentage of Salmonella spp. 10.60%; S. Auerus amounted to 30.30%; enterobacteria at 24.84%; L. monocytogenes at 3.03%; and clostridium sulfate at 1.5%. It could not been found any contamination of Campylobacter spp. in the samples.